IMPLIKASI PENGENDALIAN INTERNAL DAN TATA KELOLA DALAM PENCEGAHAN KECURANGAN PADA PERANGKAT PEMERINTAH DAERAH - Syahbana, Monang; Novita, Novita (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2020)
The purpose of this study is to determine the implications of Internal Control and Governance for the prevention of fraud. There are 71 officials along with Pancoran Mas Sub-district staff members in Depok City and the sub-districts below it that are used as research units and as the respondent samples are 49 officials along with the Pancoran Mas Sub-District Depok staff and sub-districts below using purposive non random sampling. Data obtained from the processing of respondents' statements using a questionnaire. Data were analyzed using the Partial Least Square (PLS) method. Processed using the SmartPLS 3 program. The results of this study indicate: 1) Internal Control has a significant effect on Fraud Prevention, and 2) Governance has a significant effect on fraud prevention.